Yield and nutrient contents of cotton (Gossypium hirsutum) and sunflower (Helianthus annuus) as influenced by applied sulphur in irrigated Inceptisol - SINGH, JAGVIR; KAIRON, M S (The Indian Journal of Agricultural Sciences, 2014)
Field experiments were conducted for two years during kharif and rabi seasons of 1996-97 and 1997-98 to study the effect of applied sulphur on yield, phosphorus and sulphur contents in irrigated cotton (Gossypium hirsutum L.) and sunflower (Helianthus annuus L.) grown in rotation in a sandy loam Inceptisol at Sirsa (Haryana). Four levels of sulphur, viz 10,20,30 and 40 kg sulphur/ha in addition to 0 sulphur (control) were tested. Both the crops responded significantly up to direct application of 30 kg sulphur/ha. Sulphur application significantly increased the sulphur contents in cotton and sunflower seed and phosPhorus content in sunflower seed. The seed cotton and sunflower yield increased by 23.5 and 16.5% respectively with 30 kg sulphur/ha over the control. Similarly, sulphur contents increased from 0.30 to 0.72% in cotton seed and from 0Â·26 to 0.35% in sunflower seed with the application of 30 kg sulphur/ha. A marginal increase in phosphorus from 6Â·0-7.0 kg/ha and SO4-S from 14.0 to 17.3 kg/ha concentrations (in available form) of surface soil was noticed at the end of second year experimentation.